Study of colloidal gold nanorods in liquid dispersions using light scattering methods - Pavel V. Shalaev (Pensoft Publishers, 2021)
Five samples of liquid dispersions of colloidal gold nanorods having various aspect ratios have been studied using light scattering methods. Transmission electron microscopy has been employed as a reference method. Advantages and drawbacks of dynamic light scattering and nanoparticle tracking analysis methods for study of nanoparticle geometrical parameters and concentration, sample monodispersity degree and detection of large particle aggregations and quasispherical impurities have been demonstrated. We show that depolarized dynamic light scattering method can be used for analysis of geometrical parameters of colloidal gold nanorods in liquid dispersions. The measurement results depend largely on the presence of large impurity particles or particle aggregations in samples. In turn the presence of large particles in dispersions can be detected using dynamic light scattering methods or nanoparticle tracking analysis. Dynamic light scattering method is more sensitive to the presence of even small quantities of large impurities or aggregations in samples. The monodispersity degree of nanorod liquid dispersions can also be assessed using dynamic light scattering and nanoparticle tracking analysis methods, and the measurement results can be considered more statistically significant in comparison with electron microscopy because a larger number of particles are analyzed. An increase in the concentration of spherical particles in compound dispersions of colloidal gold nanospheres and nanorods leads to a decrease in the contribution of the rotational mode to the overall scattering intensity. Data on the concentration of quasispherical impurities in samples of colloidal gold nanorod liquid dispersions have been reported on the basis of scattered light depolarization degree measurements.